Kesesuaian Penggunaan Obat Pada Pasien Diabetes Mellitus Berdasarkan Algoritma Terapi Di wilayah Kerja Puskesmas Cendrawasih dan Puskesmas Jumpandang Baru Kota Makassar - Rusli Rusli; Arisanty Arisanty; Dwi Syah Fitra Ramadhan; Frida Bahar; Suci Ramadani (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Diabetes mellitus (DM) is a long-term multisystem disease characterized by aberrant insulin synthesis, impaired insulin use, or both. Diabetes mellitus (DM) will become increasingly common worldwide to triple by 2030. The purpose of this study was to analyze the appropriateness of drug use in patients with diabetes mellitus based on the diabetes mellitus therapy algorithm in the working area of the cendrawasih and jumpandang baru puskesmas in Makassar city. In this study the authors used the Retrospective Technique. This technique is carried out by taking data on patients with diabetes mellitus in the work area of the cendrawasih and jumpandang baru health centers in the city of Makassar. The results of the study using 67 medical record samples at the cendrawasih health center found that most patients in this study were female (68.65%), age> 60 years (56.72%), last high school education (38.81%), IRT work (49.25%). The most common group of antidiabetic drugs is Biguanide with the most common drug metformin (63.44%). The most common therapy pattern is Biguanide Metfromin group monotherapy (93.33%), the most use of combination therapy is Sulfonylurea and Biguanide groups, namely Metformin and Glimepiride (40.91%). The suitability of the selection of antidiabetic drugs for all patients is said to be in accordance with PERKENI (2021) as many as 67 patients (76.87%) while the results of this study using 75 medical record samples at jumpandang baru health center found that most patients in this study were female with an age range of 45-64 years (69.23%). The most commonly used antidiabetic drug class is the biguanide group, namely metformin (53.57%). The most common therapy pattern was metformin monotherapy (71.05%). For the use of two-drug polatherapy with the most combinations, namely the biguanide group (metformin) with the sulfonylurea group (glimepirid) with a percentage of (75.67%). Keywords: antidiabetics drugs, diabetes mellitus, and appropriateness of drug use.